4
$\begingroup$
xxx=(2 Sqrt[1 - 2/(1 + Sqrt[G1])] G1 + 
 2 Sqrt[((-1 + Sqrt[G1]) G1)/(1 + Sqrt[G1])])/(-1 + 2 G1)

I have quite complicated expression. I want to simplify little better. I tried

FullSimplify[xxx, TransformationFunctions -> {Automatic, PowerExpand},
  Assumptions -> {G1 > 1}]

You can see that is can be simplified to by hand

(2 Sqrt[-1 + G1] Sqrt[G1])/(-1 + 2 G1) 

however, it does not work in this case. Any suggestion?

$\endgroup$
4
$\begingroup$

Weirdly, the less specific assumption $G1>0$ works to achieve your simplification here:

Simplify[xxx, Assumptions -> G1 > 0]

simpler result, as requested

|improve this answer|||||
$\endgroup$
  • $\begingroup$ It is very strange, but it helps a lot! thank you $\endgroup$ – Saesun Kim Jan 13 at 15:35
0
$\begingroup$

An other way is avoiding square roots.

FullSimplify[xxx /. G1 -> g2^2, Assumptions -> g2 > 1] /. 
      g2 -> Sqrt[G1]

enter image description here

|improve this answer|||||
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.